Saving Saba bank: policy implications of biodiversity studies. - Paul C Hoetjes; Kent E Carpenter (PLoS ONE, 2010)
Saba Bank has always been an area of special importance to the neighboring island of Saba in the Netherlands Antilles. Sabans traditionally fished on the Bank as far back as 1907, but increasing foreign fishing pressures on the Bank in the 1970s and 1980s forced many Saban fishermen out. Concerns were compounded by the suspicion that shipping was also damaging the benthic habitat of the bank. Fishery legislation, enacted in 1996, brought an end to unlicensed fishing and established Coast Guard enforcement on the Bank, but also led to protests from neighboring countries that previously fished on the Bank.Research was necessary to support the need for protection. Review of available research of Saba Bank and rapid biological assessments and fisheries surveys since 1996 emphasized the richness of Saba Bank's biodiversity and the need for protection of fisheries stocks. The national nature policy plan recognized this and encouraged further research to base conservation measures on.Recent biological surveys of corals, fishes, and algae presented in this collection of articles emphasized habitat heterogeneity and the relative richness of the marine flora and fauna. These assessments formed the basis for a management plan to protect Saba Bank's biodiversity and a draft proposal to the International Maritime Organization (IMO) seeking Particularly Sensitive Sea Area (PSSA) status for the Bank. The intention of the PSSA proposal is to protect the benthic habitat on Saba Bank from anchor damage. This paper serves to provide the context for the results of the recent biodiversity surveys of Saba Bank. It is hoped that this collection will serve as a knowledge baseline and engender further research in the area.